Religion and sociological approach - BIRANE, benchaa; BENCHINE, Ahmed (Social Sciences Journal)
To address a topic of this kind, it is not possible to skip over the historical backgrounds that accompanied the religious phenomenon as a whole, whether in terms of studying the phenomenon or in terms of its developments....